The Change of Soluble Programmed Cell Death-Ligand 1 in Glioma Patients Receiving Radiotherapy and Its Impact on Clinical Outcomes - Ding, Xing-Chen; Wang, Liang-Liang; Zhu, Yu-Fang; Li, Yan-Dong; Nie, Shu-Lun; Yang, Jia; Liang, Hua; Weichselbaum, Ralph R.; Yu, Jin-Ming; Hu, Man (Frontiers in Immunology, 2020)
Background: It has been proven that the levels of soluble programmed death-ligand 1 (sPD-L1) are associated with prognosis in extracranial malignancies. However, the expression of sPD-L1 in glioma patients receiving radiotherapy (RT) remains unclear. The purpose of this study was to evaluate the concentration of sPD-L1 in the plasma of glioma patients before and after RT and to explore its relationship with clinical outcomes. Methods: Between October 2017 and September 2018, glioma patients treated with RT (30 ± 10 Gy, 2 Gy/f) were enrolled, and blood samples were collected before and after RT. We quantified the sPD-L1 levels by enzyme-linked immunosorbent assay (ELISA). The isocitrate dehydrogenase-1 (IDH-1) promoter status and Ki-67 expression of tumors were evaluated by immunohistochemistry. Glioma murine model were used to address whether circulating sPD-L1 molecules are directly targeted by an anti-PD-L1 antibody. The associations between sPD-L1 and clinical features were assessed with Pearson’s or Spearman’s correlation analysis. The progression-free survival (PFS) and overall survival (OS) were determined by the Kaplan-Meier method. Results: Sixty glioma patients were included, with a median age of 52 years. The proportions of grade I, II, III, and IV gliomas were 6.7%, 23.3%, 28.4% and 41.6%, respectively. The baseline sPD-L1 levels were significantly associated with tumor grade, IDH-1 mutation status and Ki-67 expression. Using 14.35 pg/mL as the cutoff, significantly worse PFS and OS were both observed in patients with higher baseline levels of sPD-L1 (P = 0.027 and 0.008, respectively). RT significantly increased the mean level of sPD-L1 (P < 0.001). Further analysis showed that the level of sPD-L1 in IDH-1 mutation patients was higher than that in wild-type patients. Furthermore, an analysis of glioma murine model indicated that anti-PD-L1 antibody combine with RT can be a potentially powerful cancer therapy. Conclusion: This study reported that sPD-L1 might be a potential biomarker to predict the outcome in glioma patients receiving RT. The elevated level of sPD-L1 after RT suggested that the strategy of a combination of immune checkpoint inhibitors and RT might be promising for glioma patients, especially for those with IDH-1 mutations.